Synthesis Of Silica Nanocolloids Drug Delivery System By Micelle Formation Approach - Wab, Hajarul Azwana Binti (2013)
Silica nanoparticles (NPs) colloids were synthesized by using the micelle formation approach. This method was beneficial to produce monodispersed silica NPs with 20 nm to 160 nm size range by varying the reaction temperature and volume of co-solvent 2-butanol. Non-ionic surfactant Tween 80 was used to form micelles structure to entrapped drug and directly assists in the formation of sphere silica NPs colloids DDS. Compared to other methods, this method offers an easy process of drug loading whereby the drug molecules are directly entrapped inside the micelle structure before the formation of silica NPs. In this work, a small amount of surfactant was used without additional functionalizer. Besides, the success rate of drug entrapment in silica NPs was promising with removal of surfactant was completed by dialysis process which did not affect the properties of colloidal silica NPs. The optimum volume of Si precursor (VTMS) is 2 ml. Increase amount of Si precursor formed bimodal distribution. Two Tuberculosis drug, Isoniazid drug (water soluble) and Rifampicin drug (poor water soluble) were chosen as drug model. Stability of 50 nm and 70 nm silica NPs with entrapped Rifampicin drug (SiRIF) in various concentration of Sodium Chloride (NaCl) solution and mouse serum volume percentages were tested. Release profile of 50 nm and 70 nm SiRIF in various Phosphate buffer solution (PBS) and pH (pH 1.4, pH 7.4 and pH 6.8) were compared. 70 nm SiRIF showed slower release (31 %) compared to 50 nm SiRIF (44 %) for 5 days. IC50 results from toxicity test WST-1 assays on osteosarcoma cells showed size dependent whereby smaller nanoparticles lead to higher toxicity.